PENGARUH KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SIGI - Padendenan, Yohana (Katalogis, 2017)
The study aims to determine and analyze simultaneous and partial influence of competency and career development on officalsâ€™ performance in The Department of Education and Culture, Sigi District. Sample of 27 officials selected with census method. Type of study is decriptive causal; data is analyzed with multiple linear regressions analysis. The result shows that competency and career development simultaneously and partially have significant influence on officialsâ€™ performance in The Departement of Education and Culture of Sigi District.Â